2022
DOI: 10.1155/2022/1449758
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Prognostic Nutritional Index and Neutrophil-to-Lymphocyte Ratio in Prediction of the Development of Sepsis-Induced Kidney Injury

Abstract: Background. Sepsis-related acute kidney injury (S-AKI) is a frequent complication of hospitalized patients and is linked to increased morbidity and mortality. Early prediction and detection remain conducive to optimizing treatment strategies and limiting further insults. This study was aimed at evaluating the potential predictive value of the combined prognostic nutrition index (PNI) and neutrophil-to-lymphocyte ratio (NLR) to predict the risk of AKI in septic patients. Methods. In this retrospective study, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…CRP, PCT dan NLR berkorelasi signifikan dengan kadar kreatinin (p<0,001); PCT menunjukkan koefisien korelasi tertinggi (r=0,414), sedangkan MAP menunjukkan korelasi yang lebih lemah (r=0,044). 29 Harjana et al melihat perbedaan nilai NLR dan serum sydencan-1 pada jam ke-1, 6, dan 24 pada pasien AKI sepsis, didapatkan nilai NLR pada jam tersebut lebih tinggi pada kelompok AKI sepsis dibandingkan dengan pasien non AKI (jam ke-1: 33,0±11,3 vs 15,9±2,6; jam ke-6: 19,3±3,8 vs 14,2±1,8; dan jam ke-24: 19,9±3,8 vs 11,6±1,3) (p <0,00). 31 Prado et al pada studinya untuk mengetahui peran NLR dalam memprediksi kejadian AKI pada 125 pasien sepsis di ICU menunjukkan signifikansi NLR dalam mendeteksi AKI dan jika dikaitkan dengan nilai klinis, kelompok dengan nilai NLR tinggi yaitu median 32,6 memiliki LOS yang lebih panjang.…”
Section: Analisis Perubahan Nilai Nlr Pada Kelompok Akiunclassified
“…CRP, PCT dan NLR berkorelasi signifikan dengan kadar kreatinin (p<0,001); PCT menunjukkan koefisien korelasi tertinggi (r=0,414), sedangkan MAP menunjukkan korelasi yang lebih lemah (r=0,044). 29 Harjana et al melihat perbedaan nilai NLR dan serum sydencan-1 pada jam ke-1, 6, dan 24 pada pasien AKI sepsis, didapatkan nilai NLR pada jam tersebut lebih tinggi pada kelompok AKI sepsis dibandingkan dengan pasien non AKI (jam ke-1: 33,0±11,3 vs 15,9±2,6; jam ke-6: 19,3±3,8 vs 14,2±1,8; dan jam ke-24: 19,9±3,8 vs 11,6±1,3) (p <0,00). 31 Prado et al pada studinya untuk mengetahui peran NLR dalam memprediksi kejadian AKI pada 125 pasien sepsis di ICU menunjukkan signifikansi NLR dalam mendeteksi AKI dan jika dikaitkan dengan nilai klinis, kelompok dengan nilai NLR tinggi yaitu median 32,6 memiliki LOS yang lebih panjang.…”
Section: Analisis Perubahan Nilai Nlr Pada Kelompok Akiunclassified
“…On the one hand, several novel biomarkers had been developed to improve diagnostic sensitivity and specificity of SA-AKI. Frustratingly, these biomarkers mostly are prohibitively expensive for widespread clinical use [ 6 ]. On the other hand, some researchers have established predictive models for AKI in septic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that PNI is a reliable biomarker for predicting early prognosis in patients with malignant tumors (18,19). In addition, previous studies have demonstrated that PNI or NLR is a biomarker for predicting survival and mortality rates of patients with sepsis-induced acute kidney injury (AKI) (20,21). In addition, procalcitonin (PCT) and C-reactive protein (CRP) are known to be used to diagnose sepsis and predict its severity and mortality in patients (22,23).…”
Section: Introductionmentioning
confidence: 99%